Complexidades do saneamento básico e sáude pública - Matos, Camila Soares Cardoso de (2020)
The sanitation action, in addition to being fundamentally a public health and environmental protection action, is also a collective consumption good, an essential service, a fundamental right of the citizen and a duty of the State. Sanitation, as an instrument for health promotion, presumes the overcoming of technological, economic, political and managerial barriers that have made it difficult to extend the benefits to residents of rural areas, small municipalities and, mainly, to peri-urban areas and agglomerations. major Brazilian metropolises, becoming one of the main challenges today. Environmental and health aspects are closely linked to the social, economic, legal and institutional context, where factors such as the average household income, gross domestic product, education, social inclusion and housing conditions are decisive for achieving better conditions human and environmental health and, in effect, quality of life. Initially, the complexities of the basic sanitation sector with regard to public policies and the institutional aspects of the provision of basic sanitation services in Brazil will be examined, as well as the sanitation plans recommended by the National Basic Sanitation Policy, regulation and regulatory models the sanitation sector and the management models of basic sanitation services in Brazil. In the second section, sanitary sewage in Brazil, the sector's situational diagnosis and the interface with public health will be discussed. In the third, the new legal framework for basic sanitation in Brazil will be analyzed with regard to the main changes and the debate about universal access and re-statation measures that have occurred in the last twenty years around the world, whether by provoking planners to place in practice tools, strategies, plans and programs, in order to rationalize investments and disparities, local and regional, whether due to the possibility of them idealizing, planning, formulating and implementing public, intersectoral and integrated policies that make resources more efficient and productive. applied, from the perspective of citizenship.